TREM DA SERRA: A(S) SAGA(S) POÉTICA(S) DO(S) IMIGRANTE(S) ITALIANO(S) NA SERRA GAÚCHA - de Godoy, Ana Boff (Organon, 2003)
This paper is an analysis of the prosaic poem Trem da serra:poema da região colonial italiana, written by the South-Brazilian writerErnani Fornari, under the light of travel literature. The travel, here, isseen not only as the spatial physical displacement of the narrator poet butalso as a displacement throughout time both of the period of the travelitself, and of the time of memory, which is revisited while the train rollsthrough the beautiful landscape of Brazilian southern mountains. Moreover,following the situation presented by the author himself, the travel isalso analyzed in terms of the identity quest lived by the son of Italian immigrants,who wavers between two cultures.